2010
DOI: 10.1002/bit.22924
|View full text |Cite
|
Sign up to set email alerts
|

Primary rat hepatocyte culture on 3D nanofibrous polymer scaffolds for toxicology and pharmaceutical research

Abstract: Primary rat hepatocytes are a widely used experimental model to estimate drug metabolism and toxicity. In currently used two-dimensional (2D) cell culture systems, typical problems like morphological changes and the loss of liver cell-specific functions occur. We hypothesize that the use of polymer scaffolds could overcome these problems and support the establishment of three-dimensional (3D) culture systems in pharmaceutical research. Isolated primary rat hepatocytes were cultured on collagen-coated nanofibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…For example, primary hepatocytes and chondrocytes will lose their normal phenotype in monolayer culture, but this loss can be reversed simply by growing these cells into 3D spheroids. 9,10 Aggregation of cells such as myoblasts has also been shown to promote cell viability and proliferation. 11 Human mesenchymal stem cells (hMSCs) are multipotent cells with many useful attributes such as their proliferative capacity in vitro and immunomodulatory abilities in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…For example, primary hepatocytes and chondrocytes will lose their normal phenotype in monolayer culture, but this loss can be reversed simply by growing these cells into 3D spheroids. 9,10 Aggregation of cells such as myoblasts has also been shown to promote cell viability and proliferation. 11 Human mesenchymal stem cells (hMSCs) are multipotent cells with many useful attributes such as their proliferative capacity in vitro and immunomodulatory abilities in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that 3D culture techniques based on aggregates, spheroids and tissue scaffolds or hydrogels help cells to retain their natural functionality. For instance, it was demonstrated that hepatocytes can exclusively maintain their physiologically relevant phenotype within a three-dimensional context (Bierwolf et al, 2011).…”
Section: Microfluidic 3d Cell Microarraysmentioning
confidence: 99%
“…Compared with conventional monolayer culture, spheroid cultures are considered to provide microenvironments more closely related to in vivo conditions [16,17]. For example, primary hepatocytes and articular chondrocytes maintained their organ-specific functions when they were cultured as spheroids but not when grown in monolayer cultures [18]. Various spheroid fabrication techniques that employ nonadherent surfaces [19], spinner flasks [20], hanging drop methods [21], micropatterning of cell-adhesive/non-adhesive surfaces [22,23], and micromolding [24,25] have been reported.…”
Section: Formation and Collection Of Spheroidsmentioning
confidence: 99%